(untitled) (Research, Society and Development, 2020)
To verify the association between the feeding of infants under 180 days of age beneficiaries of the Bolsa Família Program (PBF) and the occurrence of wheezing. Cross-sectional research. The population consisted of children younger than 180 days, attended in 11 units of the Family Health Strategies (ESF), in the city of Santa Maria, Rio Grande do Sul. Data collection was obtained at the time of the mandatory annual weighings of the PBF. A standardized questionnaire was used and the Food Consumption Markers and the Written Questionnaire - International Study of Wheezing in Infants (QE-EILS) were included. For data analysis, the chi-square test and the prevalence ratio (PR) with a 95% confidence interval (CI) were used. The level of significance adopted was 5%. A total of 47 infants were evaluated with a mean age of 123.49 ± 55.54 days, 24 (51.1%) of whom were male. As for the QE-EILS, 26 (55.3%) infants have family members with asthma and 23 (48.9%) had wheezing in the last six months. There was a statistically significant association between wheezing in the last six months and consumption of breast milk (PR 0.45; 95% CI: 0.32-0.63), (p = 0.021), fruit juice (PR 1.85; 95% CI: 1.14-2.99), (p = 0.039), fruit (RP 2.08; 95% CI: 1.29-3.36), (p = 0.010) and salt food (RP 1 , 96; 95% CI: 1.21-3.16), (p = 0.020). Children who did not receive breast milk, and those who received fruits, salt food, cow’s milk, juice and water in the first 180 days of life had a higher prevalence of wheezing and other respiratory symptoms, which is why it is important to encourage recommendations adequate food and nutrition in childhood.